Pengaruh Kepiawaian Guru Dan Unsur Orang Tua Dalam Upaya Meningkatkan Mutu Pendidikan - Iwan Ridwan; Suaidi Suaidi (Jurnal Sadewa : Publikasi Ilmu Pendidikan, Pembelajaran dan Ilmu Sosial, 2023)
National development in the field of education is an effort to brighten the life of the nation and improve the quality of Indonesian people who are faithful, devout and have noble character and master science, technology and art in realizing an advanced, just, prosperous and civilized society based on Pancasila and the Constitution. -The 1945 Constitution of the Republic of Indonesia. The aim of educational development is to make Indonesian people intelligent and devoted to God Almighty. The involvement of teachers and parents of students has a huge contribution in realizing quality education. This research aims to determine the contribution of parents and teachers in building synergy in efforts to realize quality education.